2011
DOI: 10.5731/pdajpst.2011.00745
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Degradation and Impurity Characterization in rhPTH (1-34) during Stability Studies

Abstract: Unlike currently licensed therapies to manage osteoporosis, parathyroid hormone (PTH) and its analogs represent a new class of anabolic agents, which act primarily to inhibit bone resorption and remodeling. The hormone's recombinant form is a bioactive peptide, 1-34 residues, which is inherently very unstable. Prior understanding of the molecular degradation pathway will help in development of a process that will yield a better product with respect to its quality and stability. The current work focuses on deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Teriparatide is highly sensitive to the various degradation processes, like oxidation or deamidation [14][15][16], which may influence the binding affinity and the biological activity [17]. Similar impurity profile of RGB-10 and RMP was observed with chromatographic methods that included RP-and IEX-HPLC.…”
Section: Discussionmentioning
confidence: 94%
“…Teriparatide is highly sensitive to the various degradation processes, like oxidation or deamidation [14][15][16], which may influence the binding affinity and the biological activity [17]. Similar impurity profile of RGB-10 and RMP was observed with chromatographic methods that included RP-and IEX-HPLC.…”
Section: Discussionmentioning
confidence: 94%
“…Recent US Food and Drug Administration (FDA)-approved medications for osteoporosis, such as recombinant human parathyroid hormone peptide (rhPTH 1-34) (trade name: Forteo ® ), have been shown to be effective in treating osteoporosis [47]. However, they can be problematic because, for example, rhPTH 1-34 can degrade during its shelf life [48]. These observations suggest that small molecules could be utilized as alternative novel bone anabolic agents for the treatment of osteoporosis.…”
Section: Preclinical Studies and Potential Clinical Applicationsmentioning
confidence: 99%
“…Kothari et al [30] evaluated degradation products formed during storage of the recombinant human parathyroid hormone. They found that the hormone degraded because of not only oxidation but also deamidation and peptide bond cleavage.…”
Section: Protein Degradationmentioning
confidence: 99%
“…Silva et al [32] examined the structural integrity of preparations of interferon alfa-2a (IFN-α2a) and interferon alfa-2b (IFN-α2b), which had been ProTEIN AggrEgATIoN 527 FIGURE 13.5 reverse-phase high-performance liquid chromatography (rP-hPlc) chromatogram of drug product (recombinant human parathyroid hormone) stored for 6 months at (a) 5 ± 3°c and (b) 25 ± 2°c [30]. …”
Section: Protein Aggregationmentioning
confidence: 99%
See 1 more Smart Citation